SELECTION AND CHARACTERIZATION OF SIDEROPHORE-PRODUCING RHIZOBACTERIA AND POTENTIAL ANTAGONISTIC ACTIVITY TOWARD Ralstonia solanacearum - Abdjad Asih Nawangsih; Ida Parida; Suryo Wiyono; Juang Gema Kartika (SEAMEO BIOTROP, 2017)
Ralstonia solanacearum is an important pathogen of tomato. An alternative method to control this disease is through the application of biocontrol agents. Plant Growth-Promoting Rhizobacteria (PGPR) can be used as potential biocontrol agents, and PGPR producing siderophores play an important role in disease suppression. This experiment was conducted to select and characterize siderophore-producing rhizobacteria from tomato and to determine their potential as antagonistic agents against R. solanacearum. Candidates of PGPR were isolated from tomato plants grown in West Java Province, Indonesia. The isolates were screened for siderophore production using CAS medium. Among the 29 siderophore-producing isolates that showed a negative hypersensitivity reaction, two isolates exhibited the widest inhibition zones against R. solanacearum. These isolates were CP1C and CP2D, with inhibition zone diameters of up to 3.6 mm and 7.0 mm, respectively. Based on 16S rDNA sequencing, isolate CP1C was identified as Brevundimonas sp., while isolate CP2D was identified as Enterobacter sp. Both isolates did not negatively affect plant height or plant dry weight when compared with the control.